Population dynamics of yellowtail scad, Atule mate (Cuvier 1833) in Marudu Bay, Sabah, Malaysia - M. K., Mohd Azim; Sarker, S. M. Nurul Amin Harmuj Ali; Romano, Nicholas Paul; Arshad, Aziz; Md. Yusoff, Fatimah (Penerbit Universiti Kebangsaan Malaysia, 2017)
The yellowtail scad, Atule mate, forms important fisheries throughout the Indo-Pacific region. To know about the stock status of A. mate in Malaysia, various population parameters were measured, by utilizing length-frequency data, that included asymptotic length (L∞), growth coefficient (K), mortality rates (Z, F and M), exploitation level (E) and recruitment pattern of this species from Marudu Bay, Sabah, Malaysia. Total length and body weight relationship was estimated as W = 0.007TL3.148 (R2 = 0.937). The asymptotic length (L∞) and growth coefficient (K) were estimated 27.80 cm and 1.50 yr−1, respectively. Total mortality (Z), natural mortality (M) and fishing mortality (F) were found to be 4.53, 2.46 and 2.07 yr−1, respectively. The exploitation level (E) was estimated 0.46. It was showed that the recruitment pattern was continuous with two major peaks per year. Relative yield per recruit predicted a maximum exploitation rate (Emax) which was 0.55. The current E value (0.46) is lower than the optimum exploitation (E = 0.50) as well predicted Emax. Therefore, it could be concluded that stock of A. mate in the investigated area of Marudu Bay, Sabah is under exploited.